Multiset FMRI Data Analysis with Subject Group Information using Structured Dictionary Learning - Xu, Shuai; Jin, Rui; Kim, Seung-Jun; Calhoun, Vince D.; Adali, Tulay (Proceedings (International Symposium on Biomedical Imaging), 2025)
A dictionary learning (DL)-based method for analyzing multiple functional magnetic resonance imaging (fMRI) data sets is developed. The algorithm can incorporate subject group information to extract neural activation maps indicative of the group differences and the maps shared across groups. Furthermore, multiple data sets are jointly analyzed to obtain the maps common across data sets and those unique to individual data sets. For this, a novel structured supervised DL problem is formulated. Numerical tests on synthetic and real fMRI data sets verify the effectiveness of the proposed method